ChemInform Abstract: Enantioselective Transformation of Allyl Carbonates into Branched Allyl Carbamates by Using Amines and Recycling CO2 under Iridium Catalysis. Issue 48 (2nd December 2014) - Zheng, Sheng‐Cai; Zhang, Min; Zhao, Xiao‐Ming
Abstract A domino reaction of allyl carbonates and amines is developed to yield enantioenriched branched allyl carbonates.